Relationships Between Anxiety, Perceived Vulnerability to Disease, and Smartphone Use During Coronavirus Disease 2019 Pandemic in a Sample of Italian College Students - De Pasquale, Concetta; Pistorio, Maria Luisa; Sciacca, Federica; Hichy, Zira (Frontiers in Psychology, 2021)
Introduction As of March 2020, Coronavirus disease SARS-coV-2 (COVID-19) has been declared a "pandemic" by the WHO. This has led to the need for governments around the world to implement restrictive containment and isolation measures to stem the spread of the virus; these measures have included social distancing, isolation, and quarantine. The fear of contagion has been indicated as one of the causes of stress, anxiety, depression, and insomnia in the general population. The aim of our study was to explore, in a sample of Italian university students, the relationships between anxiety, perceived vulnerability to disease, and smartphone use during the COVID-19 pandemic. Methods A sample of 194 volunteer college students were recruited to participate in the study. Participants were recruited via an online questionnaire sent to students of the University of Catania (Italy) and distributed from September 2020 to January 2021. The volunteer participants were given an online protocol that included the Fear of COVID-19 Scale (FCV-19S) for evaluation of fear, the Perceived Vulnerability to Disease (PVD) to evaluate perceived vulnerability to disease, the State Trait Anxiety Inventory (STAI) for evaluation of trait and state anxiety, and the Smartphone Addiction Scale Short Version for Adolescents and Young Adults (SAS- SV) to evaluate use, abuse, or addiction of smartphone use. Results University students showed moderate trait and state anxiety (score of 51.60 in TAI and score of 47.21 in SAI) in STAI. In addition, students showed moderate perceived vulnerability to disease (score of 51.51) in PVD. The results showed that fear of COVID-19 and Trait Anxiety appear to be predictors of State Anxiety (SAI) and Perceived Vulnerability to Disease (PVD), but to be not predictors of risk Smartphone Addiction (SAS-SV). Conclusion The data highlighted the presence of a perception of vulnerability to infections in subjects in which there was also a moderate anxiety, both state and trait, associated with the fear of the COVID-19 pandemic. The possible positive role of the use of smartphones in maintaining social contacts should also be emphasized.